1980
DOI: 10.1111/j.1365-246x.1980.tb04817.x
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic lunar analysis by least-squares

Abstract: A simple and accurate method is presented for the determination of lunar and solar harmonic terms present in a series of geomagnetic data. It is based on least-squares and incorporates a direct means for determining the confidence limits. The method is tested by applying it to a series of artificially generated data, and comparing the results both with the true answers and with results obtained using existing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…This is closely similar to that described by Malin and Schlapp (1980). For a given observatory, each nighttime mean provides an equation of condition of the form H (t) = H 0 + a 0 t + a 1 cos t + b 1 sin t + a 2 cos 2t + b 2 sin 2t, where t increases from 0 to 2π from January 0.0 to December 31.0, H 0 represents a constant term, a 0 t the secular variation (assumed to be linear over the 2-year interval analysed), a 1 cos t +b 1 sin t the annual variation and a 2 cos 2t +b 2 sin 2t the semi-annual variation.…”
Section: Methods Of Analysissupporting
confidence: 78%
“…This is closely similar to that described by Malin and Schlapp (1980). For a given observatory, each nighttime mean provides an equation of condition of the form H (t) = H 0 + a 0 t + a 1 cos t + b 1 sin t + a 2 cos 2t + b 2 sin 2t, where t increases from 0 to 2π from January 0.0 to December 31.0, H 0 represents a constant term, a 0 t the secular variation (assumed to be linear over the 2-year interval analysed), a 1 cos t +b 1 sin t the annual variation and a 2 cos 2t +b 2 sin 2t the semi-annual variation.…”
Section: Methods Of Analysissupporting
confidence: 78%
“…Stening et al (1997b) compared least- squares fitting of a sum of solar and lunar tides to geophysical time series (Malin and Schlapp, 1980) in comparison to methods based on Fourier analysis (Winch and Cunningham, 1972) and concluded that the least-squares method offers a number of advantages. In particular, each hourly data point is treated separately, so scattered and/or missing data is not a problem.…”
Section: Discussionmentioning
confidence: 99%
“…The location of Collm differs in longitude by 17 • from the UK. This difference is accounted for using the analysis method described by Malin and Schlapp (1980) (i.e. the phases, time of maximum, should be directly comparable for the migrating lunar tide).…”
Section: Discussionmentioning
confidence: 99%
“…In 1980, the least-squares method was originally introduced and compared with the method of Chapman-Miller by Malin and Schlapp (1980). Compared with the other lunar tidal analysis method, they found that the least-squares method has several advantages.…”
Section: Discussionmentioning
confidence: 99%